Tinjauan Penerapan Sistem Manajemen Keselamatan Dan Kesehatan Kerja (SMK3) Pada Proyek Pembangunan Gedung Berdasarkan PP No. 50 Tahun 2012 (Studi Kasus : Pembangunan Gedung Telkomsel Pekanbaru) (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The growth of economy in Pekanbaru is taking the private sector to participate in the development of Pekanbaru city. One of the example is the construction of Network Buiding of Pekanbaru. This project is an interesting project to observed due to the stature of Telkomsel as a giant company that has worked on the flield of construction for over than 50 years and employing 100 works which are having high risk of work accident. Therefor it is necessary to conduct a research about the evaluation of SMK3 application on those project in accordance with PP N0.50 Tahun 2012 thus the work accident can be reduced to minimum. The method used in this research is quantitative method, Univariat analysis and qualitative descriptive. Quetioner are distributed to 19 respondent for staffs and 108 respondent for workers. This research yields the results of evaluation for the level of succes for SMK3 application at 77,01% which is classified in category two with the range of accomplishment at 60-84% meaning good achievement. As for the succes level of SMK3 Audit result, the value is obtained at 84,34% and classified in good application with 24 minor incompatibility. The factors that affect the workers in the application of SMK3 is psycology factor and the condition o project environment.Keywords: Network Building, Telkomsel, SMK3, Evaluation, Audit.